Identification and functional characterization of the sugarcane (Saccharum spp.) AMT2-type ammonium transporter ScAMT3;3 revealed a presumed role in shoot ammonium remobilization - Maniero, Rodolfo A.; Koltun, Alessandra; Vitti, Marielle; Factor, Bruna G.; de Setta, Nathalia; Câmara, Amanda S.; Lima, Joni E.; Figueira, Antonio (Frontiers in Plant Science, 2023)
Sugarcane (Saccharum spp.) is an important crop for sugar and bioethanol production worldwide. To maintain and increase sugarcane yields in marginal areas, the use of nitrogen (N) fertilizers is essential, but N overuse may result in the leaching of reactive N to the natural environment. Despite the importance of N in sugarcane production, little is known about the molecular mechanisms involved in N homeostasis in this crop, particularly regarding ammonium (NH4 + ), the sugarcane´s preferred source of N. Here, using a sugarcane BAC library and a series of in silico analyses, we identified an AMMONIUM TRANSPORTER (AMT) from the AMT2 subfamily, sugarcane AMMONIUM TRANSPORTER 3;3 (ScAMT3;3), that is constitutively and highly expressed in young and mature leaves. To characterize its biochemical function, we ectopically expressed ScAMT3;3 in heterologous systems (Saccharomyces cerevisiae and Arabidopsis thaliana). The complementation of triple mep mutant yeast demonstrated that ScAMT3;3 is functional for NH3/H + cotransport at high availability of NH4 + and under physiological pH conditions. The ectopic expression of ScAMT3;3 in the Arabidopsis quadruple AMT knockout mutant restored the transport capacity of 15 N-NH4 + in roots and plant growth under specific N availability conditions, confirming the role of ScAMT3;3 in NH4 + transport in planta. Our results indicate that ScAMT3;3 belongs to the low-affinity transport system (Km 270.9 µM; Vmax 209.3 µmol g -1 root DW h -1 ). We were able to infer that ScAMT3;3 plays a presumed role in NH4 + source-sink remobilization in the shoots via phloem loading. These findings help to shed light on the functionality of a novel AMT2-type protein and provide bases for future research focusing on the improvement of sugarcane yield and N use efficiency.